PENGENALAN SISTEM INTERNET OF THINGS (IOT) BERBASIS ARDUINO DI SMA NEGERI 1 BREBES - Fitria, Ria Indah; Prasetyo Tulodo, Rizki; Tulus Ujianto, Nur; Sofian, Ali (STKIP PGRI SITUBONDO, 2024)
The internet of things is a concept or program where an object has the ability to transmit or send data over a network without using the help of computer devices and humans. The internet of things or often called IoT is currently experiencing a lot of development. The introduction of an Arduino-based Internet of Things (IOT) system at SMA Negeri 1 Brebes helped students there to develop the system. We here want to introduce students to how Arduino functions in today's modern era. Apart from function, we also introduce how Arduino works and how to operate Arduino in a school environment. One example that Arduino can use in a school environment is attendance by detecting faces or you can use the retina of the eye. There are many examples that can be taken from case studies on the use of Arduino which can be applied to the SMA Negeri 1 Brebes school environment. The introduction of Arduino has many benefits for students at the school, because students can have many ideas that can be developed to make their school more modern or can also create works which will then be published to introduce their school to the wider community. . Students can have lots of ideas that they want develop and also because the equipment used in making the Arduino system is very affordable. Apart from Arduino's affordable price, finding equipment is not that difficult, because there are lots of people who sell Arduino equipment widely, either offline in computer shops or even online, which is sold freely.